Evolution of defect structures leading to high ZT in GeTe-based thermoelectric materials - Jiang, Yilin; Dong, Jinfeng; Zhuang, Hua-Lu; Yu, Jincheng; Su, Bin; Li, Hezhang; Pei, Jun; Sun, Fu-Hua; Zhou, Min; Hu, Haihua; Li, Jing-Wei; Han, Zhanran; et al. (Nature communications, 2022)
GeTe is a promising mid-temperature thermoelectric compound but inevitably contains excessive Ge vacancies hindering its performance maximization. This work reveals that significant enhancement in the dimensionless figure of merit ( ZT ) could be realized by defect structure engineering from point defects to line and plane defects of Ge vacancies. The evolved defects including dislocations and nanodomains enhance phonon scattering to reduce lattice thermal conductivity in GeTe. The accumulation of cationic vacancies toward the formation of dislocations and planar defects weakens the scattering against electronic carriers, securing the carrier mobility and power factor. This synergistic effect on electronic and thermal transport properties remarkably increases the quality factor. As a result, a maximum ZT > 2.3 at 648 K and a record-high average ZT (300-798 K) were obtained for Bi 0.07 Ge 0.90 Te in lead-free GeTe-based compounds. This work demonstrates an important strategy for maximizing the thermoelectric performance of GeTe-based materials by engineering the defect structures, which could also be applied to other thermoelectric materials. The intrinsic high-concentration Ge vacancies in GeTe-based thermoelectric materials hinder their performance maximization. Here, the authors find that defect structure engineering strategy is effective for performance enhancement.